Green Chemistry and Education - Bassey, Obot Ime (SCHOOL SCIENCE, 2006)
GREEN CHEMISTRY has evolved from its roots in academic research to become a mainstream practice supported by academia, industry, and government. While green chemistry encompasses human health and the environment, it is guided by very specific principles of chemical practice. The interest in using green chemistry and its practices has extended internationally to become an alternative to traditional pollute-and then clean-up industrial practice in developing countries. This evolution is marked by significant contributions from institutions with different goals that are being satisfied through a common mechanism.